Madeline - Bemelmans, Ludwig, 1898-1962. (New York, N.Y. : Scholastic, Inc., 1982)
Madeline, smallest and naughtiest of the twelve little charges of Miss Clavel, wakes up one night with an attack of appendicitis.
Keywords: Sick -- Fiction; Stories in rhyme; France -- Fiction